The Influence of Work Environment, Workload, and Job Satisfaction on Turnover Intention - Damayanti, Devina Fitri; Andarini, Sonja (LPPM Universitas Jambi, 2026)
The high rate of turnover intention in the food industry’s SME sector poses a serious problem that threatens the operational stability of companies. This study focuses on the continuous employee turnover at UD Sekar Arum Sidoarjo, particularly during its peak resignation month. This study aims to analyze the influence of the work environment, workload, and job satisfaction on employee turnover intention, both simultaneously and partially. The approach used is descriptive quantitative with the multiple linear regression method. The sample consist of 55 employees of UD Sekar Arum, selected using a saturated sampling technique or census. Data were collected via a 5-point Likert scale questionnaire supplemented by field observations and unstructured interview and subsequently analyzed using IBM SPSS 25. The results indicate that, simultaneously, all three variables have a significant effect on turnover intention. Partially, the work environment does not have a significant effect because employees perceive the work environment such as air circulation, lighting, and noise levels as adequate. Workload has a negative and significant effect, meaning that aligning workload with employees’ capabilities, coupled with clear SOPs and sufficient rest periods, has been shown to reduce turnover intention. Job satisfaction has a negative and significant effect.